Relaxation Time of the Particle Beam with an Anisotropic Velocity Distribution - V.P. Vechirka; S.M. Kravchenko; A.I. Kul’ment’ev; R.I. Kholodov (Журнал нано- та електронної фізики)
The computer experiment for study of the relaxation time of the beam particles with an anisotropic velocity distribution is performed by the molecular dynamics. Obtained results agree with the characteristic times of thermal relaxation in plasma for the electronic coolers in modern storage rings.